Washback Effect of the University Entrance Examination on Iranian Pre-University English Language Teachers’ Curriculum Planning and Instruction - Ghorbani, Mohammad Reza (2008)
The impact of a test on teaching and learning is commonly referred to as the washback effect. In Iran, the university entrance exam (UEE) is assumed to exert a negative washback effect on language education. This study examined the nature and scope of the impact of the UEE on pre-university English teachers’ (PETs) teaching and curricular planning in six dimensions, that is, classroom activities and time arrangement, teaching methods, teaching materials, syllabus design, teaching contents, and classroom assessment. It also explored PETs’ expectations of the UEE. In this study, eight factors (independent variables) were studied under two subheadings: 1) teacher characteristics (teaching experience, educational background, professionalism, and gender) and 2) context characteristics (school type, school location, perceived students’ learning attitudes, and perceived external pressure). In the first phase, 220 subjects selected based on the proportional stratified random sampling responded to the questionnaires. The Cronbach alpha of the questionnaire was 0.97. In the second phase, eight purposively selected PETs participated in two focus group interviews. Pearson product moment correlation coefficient, t-test statistics, and stepwise regression were used to analyze the quantitative data from the survey questionnaires and a systematic note-based technique recommended by Krueger (2002) was used to analyze and interpret the qualitative data from the focus group interviews. The findings showed that PETs’ perceived professionalism in teaching (r = .388) and perceived students’ learning attitudes (r = .464) were positively and moderately associated with their perceptions of the impact of the UEE on their instruction and curricular planning. There was also a low positive relationship between teachers’ perceived professionalism in teaching and their expectations of the UEE (r = .229). Based on the results from the stepwise regression analysis, perceived students’ learning attitudes (21.2%), perceived external pressure in teaching (3.0%), and perceived professionalism in teaching (1.1%) can be used to reliably predict PETs’ perceptions of the impact of the UEE. Furthermore, perceived professionalism (.048%) and school location (.031%) can be used to reliably predict PETs’ expectations of the UEE. Almost all PETs, regardless of their teaching experience, educational background, gender, the school type, and the school location where they were teaching perceived the negative effect of the UEE similarly. The implication is that potentially influential factors such as teachers’ experience and educational background play a neutral role in adopting effective teaching techniques due to the washback phenomenon. Thus, if the UEE is not reformed to encourage English teachers to teach communicatively, spending millions of Rials on training and improving their level of knowledge at teacher training colleges and universities would be a great loss.